The Association Between Computer Use and Cognition Across Adulthood: Use It So You Won't Lose It? - Tun, Patricia A.; Lachman, Margie E. (Psychology & Aging, 2010)
Understanding the association between computer use and adult cognition has been limited until now by self-selected samples with restricted ranges of age and education. Here we studied effects of computer use in a large national sample (N = 2,671) of adults aged 32-84, assessing cognition with the Brief Test of Adult Cognition by Telephone (Tun & Lachman, 2005) and executive function with the Stop and Go Switch Task (Tun & Lachman, 2008). Frequency of computer activity was associated with cognitive performance after controlling for age, sex, education, and health status: That is, individuals who used the computer frequently scored significantly higher than those who seldom used the computer. Greater computer use was also associated with better executive function on a task-switching test, even after controlling for basic cognitive ability as well as demographic variables. These findings suggest that frequent computer activity is associated with good cognitive function, particularly executive control, across adulthood into old age, especially for those with lower intellectual ability. Reprinted by permission of the publisher.